ANALISIS KADAR TIMBAL DALAM URIN PETUGAS OPERATOR DAN NONOPERATOR DI KECAMATAN KADEMANGAN KOTA PROBOLINGGO - Pratiwi Dewi Ika; Lestari Indah; Endarini Lully Hanni (Analis Kesehatan Sains, 2021)
Gas stations are a source of lead exposure that comes from vehicle gas emissions and petrol fuel vapors. Gas station officers, both operators and nonoperators, have a risk level of lead exposure that can enter the body and then accumulate and excreted through urine by 75-80%. Lead exposure can endanger the health of gas station officers. The purpose of this study was to analyze differences in lead levels in the urine of gas station operators and nonoperators in Kademangan District, Probolinggo City. This research is an observational study with a cross sectional method which was conducted at the Surabaya Health Laboratory Center in October 2020 - June 2021. The sample used was 15 operators and 15 nonoperators who were taken by purposive sampling. The results showed the average value of lead levels in the urine for operators 0.0007213 ppm, indoor nonoperators 0.0006386 ppm and outdoor nonoperators 0.0008263 ppm. The conclusion of this study was that there was no significant difference in lead levels in the urine of gas station operators and nonoperators.